Transformasi Pendidikan: Analisis Model Sekolah Penggerak dalam Meningkatkan Kualitas Pembelajaran di SMP Telkom Maakassar: Educational Transformation: Analysis of the Driving School Model in Improving the Quality of Learning at SMP Telkom Maakassar - AuliaIrfan; Andira Apriliyanti Amri; Fadel Rezki Adhari Mansyur; Muhammad Zainal Arifin; Arismundar; Ahlun Ansar (Pendidikan Al-Gafari, 2025)
To improve the quality of learning in Indonesia, especially at the junior high school (SMP) level, educational transformation is an important process. The